Circ-SMARCA5 suppresses colorectal cancer progression via downregulating miR-39-3p and upregulating ARID4B. Issue 12 (December 2020) - Miao, Xiaofei; Xi, Zhong; Zhang, Ye; Li, Zengyao; Huang, Longchang; Xin, Taojian; Shen, Renhui; Wang, Tong
Abstract: Background: Circular RNAs are crucial in tumorigenesis. However, little is known about their functions in colorectal cancer (CRC). Circ-SMARCA5 was found to be an oncogene or tumor suppresser in different types of cancers, but its exact role in CRC remains unknown. Here, we aim to identify the role of circ-SMARCA5 in CRC development. Methods: Circ-SMARCA5 expression was determined by qRT-PCR. CRC cell proliferation, migration, and invasion were detected by CCK-8, wound healing, and Transwell assays, respectively. Bioinformatics analysis was performed to predict target genes. The interaction of microRNA (miR) with circ-SMARCA5 or target genes was detected using luciferase reporter assay. Xenograft model was established to determine the effect of circ-SMARCA5 on CRC tumor growth in vivo . Results: Circ-SMARCA5 expression was dramatically decreased in CRC cell lines and tissues. Circ-SMARCA5 overexpression inhibited CRC cell proliferation, migration and invasion. MiR-93–3p was predicted as a target of circ-SMARCA5 and its overexpression attenuated the anti-tumor effect of circ-SMARCA5 on CRC cells. Furthermore, we predicted AT-rich interaction domain 4B (ARID4B) as the target of miR-39–3p. Functional analysis showed that circ-SMARCA5 upregulated ARID4B expression via miR-39–3p. Additionally, in vivo studies demonstrated that circ-SMARCA5 suppressed CRC tumor progression. Conclusion: Circ-SMARCA5 functions as a tumor suppressor by upregulating ARID4B expression via sponging miR-39–3p, and thereby inhibited CRC progression.